Acridones As Antiviral Agents: Synthesis, Chemical and Biological Properties - Sepúlveda, Claudia Soledad (2013)
Acridones are a class of compounds that have attracted attention in recent years for their wide range of biological properties, including selective inhibition of diverse human pathogenic viruses. The wide spectrum of antiviral activity includes DNA and RNA viruses, such as herpes simplex virus, cytomegalovirus, adenovirus, hepatitis C virus, dengue virus, and Junin virus, among others, indicative of the involvement of cellular factors as potential targets of acridone derivatives. At the present, their precise mode of action is not clearly determined, although the predominant action seems to be centered on the synthesis of nucleic acids. Regarding this point, inhibitory activity against cellular and viral enzymes and the ability to intercalate into nucleic acid molecules was demonstrated for some acridone compounds. Then, the possibility of a multiple effect on different targets renewed interest in these agents for virus chemotherapy allowing a potent inhibitory effectiveness associated to less feasibility of generating antiviral resistance. This review summarizes the current knowledge regarding the methods of synthesis, the antiviral properties of acridone derivatives, their mechanism of action, and structural characteristics related to antiviral activity as well as the perspectives of this class of compounds for clinical application against human viral infections.